PENGARUH IMPLEMENTASI MANAJEMEN KUALITAS TERHADAP KINERJA PEGAWAI PADA PUSKESMAS SE-KOTA PAYAKUMBUH - Safitri Azizah; Samsir Samsir; Daulay Nauli Iwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to look at the effect of quality management implementation on employee performance in Payakumbuh healt centers. The population in this study includes all employee at healt centers, totaling 312 people. The sample taking technique was using purposive sampling so obtained sample of 175 respondents. The dependent variable (Y) in this study was employee performance the independent variable is customer focus (X1), education and training (X2), continuous emprowerment (X3) amd teamwork (X4). The analisys method was multippled regression linier berganda. For data processing was using SPSS 23. The results showed that There significant effect of customer focus on the employee performance, there significant effect of education and training on the employee performance, there significant effect of continuous emprowerment on the employee performance and there significant effect of teamwork on the employee performance.Keywords : quality management, customer focus, education and training, continuous emprowerment, employee performance